2020
DOI: 10.1016/j.jcta.2020.105209
|View full text |Cite
|
Sign up to set email alerts
|

Counting 3-stack-sortable permutations

Abstract: We prove a "decomposition lemma" that allows us to count preimages of certain sets of permutations under West's stack-sorting map s. As a first application, we give a new proof of Zeilberger's formula for the number W2(n) of 2-stack-sortable permutations in Sn. Our proof generalizes, allowing us to find an algebraic equation satisfied by the generating function that counts 2-stack-sortable permutations according to length, number of descents, and number of peaks. This is also the first proof of this formula th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
85
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(85 citation statements)
references
References 36 publications
0
85
0
Order By: Relevance
“…If π is a permutation with largest entry m, then we can write π = LmR for some permutations L and R. Then For each positive integer n, we can view s as a discrete dynamical system on S n . We refer the reader to [2,3,6,8] and the references therein for more information about this map. In [6][7][8], the first author found methods for computing the number of preimages of an arbitrary permutation under the stack-sorting map.…”
Section: The Stack-sorting Mapmentioning
confidence: 99%
See 1 more Smart Citation
“…If π is a permutation with largest entry m, then we can write π = LmR for some permutations L and R. Then For each positive integer n, we can view s as a discrete dynamical system on S n . We refer the reader to [2,3,6,8] and the references therein for more information about this map. In [6][7][8], the first author found methods for computing the number of preimages of an arbitrary permutation under the stack-sorting map.…”
Section: The Stack-sorting Mapmentioning
confidence: 99%
“…We refer the reader to [2,3,6,8] and the references therein for more information about this map. In [6][7][8], the first author found methods for computing the number of preimages of an arbitrary permutation under the stack-sorting map. Unfortunately, it seems quite difficult to use these methods in order to find an explicit formula for deg(s : S n → S n ).…”
Section: The Stack-sorting Mapmentioning
confidence: 99%
“…This map, denoted by s, sends permutations of length n to permutations of length n. It is a slight variant of the stack-sorting algorithm that Knuth introduced in [27]. The map s was studied extensively in West's 1990 Ph.D. thesis [44] and has received a considerable amount of attention ever since [5,6,8,14]. We give necessary background results concerning the stack-sorting map in Section 3, but the reader seeking additional historical motivation should consult [5,6,14] and the references therein.…”
Section: Introductionmentioning
confidence: 99%
“…to prove, but now has several complicated proofs. See [10] , [7], [6] or [5] for various proofs. Theorem 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…For t = 3, he proved the upper bound lim n→∞ n W 3 (n) ≤ 12.53296, and for t = 4, he proved the upper bound lim n→∞ n W 3 (n) ≤ 21.97225. Results on related lower bounds can be found in Defant's paper [5], where it is shown that lim n→∞ n W 3 (n) ≥ 8.659702 and that lim n→∞ n W t (n) ≥ ( √ t + 1) 2 , along with a new proof for the formula for W 2 (n), and a polynomial time algorithm to compute the numbers W 3 (n).…”
Section: Introductionmentioning
confidence: 99%